Effect of nitrogen on growth and yield on mungbean in low nutrient soil - Razzaque, MA; Haque, MM; Karim, MA (Bangladesh Journal of Agricultural Research, 2017)
A pot experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during kharif II season of 2011 to investigate the growth, dry matter production and yield of mungbean genotypes under nutrient stress soil. Ten mungbean genotypes viz., IPSA-12, GK-27, IPSA-3, IPSA-5, ACC12890053, GK-63, ACC12890055, BARI Mung-6, BUmug- 4 and Bina moog- 5 and six nitrogen fertilizer levels viz., 0, 20, 40, 60, 80 and 100 kg N ha-1 were included as experimental treatments. Results revealed that increasing nitrogen level in nutrient stress soil increased growth and dry matter production up to 60 kg N ha-1 irrespective of genotype and thereafter decreased. Among the mungbean genotype IPSA 12 showed maximum leaf area, dry matter production and seed yield (14.22 g plant-1) in nutrient stress soil. The lowest seed yield (7.33 g plant -1) was recorded in ACC12890053 under control condition. Bangladesh J. Agril. Res. 42(1): 77-85, March 2017